Gene RB cloned from Solanum bulbocastanum confers broad spectrum resistance to potato late blight - Song, Junqi (National Academy of Sciences, 2003)
Late blight, caused by the oomycete pathogen Phytophthora infestans, is the most devastating potato disease in the world. Control of late blight in the United States and other developed countries relies extensively on fungicide application. We previously demonstrated that the wild diploid potato species Solanum bulbocastanum is highly resistant to all known races of P. infestans. Potato germplasm derived from S. bulbocastanum has shown durable and effective resistance in the field. Here we report the cloning of the major resistance gene RB in S. bulbocastanum by using a map-based approach in combination with a long-range (LR)-PCR strategy. A cluster of four resistance genes of the CC-NBS-LRR (coiled coil–nucleotide binding site–Leu-rich repeat) class was found within the genetically mapped RB region. Transgenic plants containing a LR-PCR product of one of these four genes displayed broad spectrum late blight resistance. The cloned RB gene provides a new resource for developing late blight-resistant potato varieties. Our results also demonstrate that LR-PCR is a valuable approach to isolate genes that cannot be maintained in the bacterial artificial chromosome system.